Melatonin decreases plasma TNF-α and improves nonenzymatic antioxidant defence and insulin sensitivity in rats with apical periodontitis fed a high-fat diet - dos Santos, Rodrigo Martins [UNESP]; Tsosura, Thais Verônica Saori [UNESP]; Belardi, Bianca Elvira [UNESP]; Chaves Neto, Antonio Hernandes [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Mattera, Maria Sara de Lima Coutinho [UNESP]; Tessarin, Gestter Willian Lattari; Bravo, Lara Teschi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Matsushita, Doris Hissako [UNESP] (Wiley, 2023)
Aim: To analyse the effects of melatonin (ME) treatment on oxidative stress and insulin resistance (IR) in rats with apical periodontitis (AP) fed a high-fat diet (HFD). Methodology: Eighty 60-day-old rats were divided into eight groups: control (CN), AP, HFD with AP (HFDAP), control with ME (CNME), AP with ME (APME), HFD with ME (HFDME) and HFD with AP+ME (HFDAPME). The animals from the HFD groups were fed a HFD throughout the experimental period. On day 7, the animals from the AP groups were subjected to experimental AP, and after 70 days, the ME groups were treated for 30 days. Glycaemia, insulinaemia, homeostatic model assessment for IR index, tumour necrosis factor-α (TNF-α), and interleukin-6 were analysed in plasma using biochemical tests and enzyme-linked immunosorbent assay. Thiobarbituric acid-reactive substances (TBARS), carbonyl protein (CP), superoxide dismutase (SOD), catalase, glutathione peroxidase, glutathione (GSH) and total antioxidant capacity (ferric reducing antioxidant power [FRAP]) were analysed in the gastrocnemius muscle. Results: (1) Association of AP and HDF exacerbated IR, and ME treatment improved this alteration; (2) AP and HFD and their association showed increased TNF-α, and ME reversed it; (3) TBARS increased in the AP and HFDAP groups, and ME reversed only in the group with the association of disease and diet; (4) CP increased in all HFD groups and improved in the ME groups; (5) GSH activity decreased in all experimental groups, and ME increased this parameter only in the CN and AP groups; (6) FRAP did not change between the groups, but ME treatment increased its activity in the AP and HFD groups; (7) ME increased SOD in the CN and AP groups. Conclusion: Apical periodontitis and HFD promoted IR, and the association of AP with diet promoted IR exacerbation; this resistance might have been caused by an increase in TNF-α. AP promoted more intense changes in lipid oxidative damage than in protein oxidative damage. In non-enzymatic antioxidant defence, it was observed that both AP and HFD and their association promoted a decrease in GSH levels. Overall, ME treatment reversed changes such as oxidative stress and IR.
Keywords: apical periodontitis; high-fat diet; insulin resistance; melatonin; oral health; oxidative stress